An alternative source of probiotics: Water kefir. Issue 1 (8th January 2023) - Cufaoglu, Gizem; Erdinc, Ayse Nur
Abstract: The aim of this review was to compile the origin and distribution of water kefir, its production, microbial diversity, fermentation dynamics, health effects, and its place in national/international food legislation. Water kefir is a traditional, slightly carbonated fermented beverage with a lactic acid content of up to 2%. It is obtained by fermenting sugar by kefir grains, which are white or yellowish in color and translucent in appearance. The types of microorganisms in the water kefir differ depending on the sugar, carbon sources, and fermentation conditions. It has a complex microbiota mainly consisting of lactic acid bacteria, acetic acid bacteria, and yeasts. In addition, fermented water kefir contains various metabolites, including sugar, fruit‐derived components, lactic acid, acetic acid, ethanol, carbon dioxide, mannitol, vitamins, and amino acids such as arginine. As a non‐dairy fermented beverage, water kefir emerges as an alternative source of probiotics for individuals with lactose intolerance, people with dairy allergic reactions, and vegan consumers. However, although consumer demands have driven the food industry to increase the production of water kefir, the most common production still relies on the traditional method due to some difficulties in the industrial‐scale production process. On the other hand, more in vitro and in vivo studies should be carried out to reveal the health benefits of water kefir.